Jilbab dalam al-Qur’an dan Relevansinya dengan Pendidikan Islam - Hanafy, Sain (Al-Riwayah : Jurnal Kependidikan, 2018)
This article shows that: the concept of Quran about the veil not only instructs women to wear the hijab, but also to the believing men and women of Muslims to adorn themselves with piety jewelry. The concept of the veil was ordered not to say in a voice seductive, stimulating and provoke lust, stay indoors, not out except in a situation that really needs, not tabarruj, not open-aperture, establish prayers, pay zakat, submit and obey all which Allah recommended to His Apostle to what came to him. The relevance of the concept of Qur'an about the veil with the goal of Islamic education is its compatibility in the formation of human morality that leads to the personality of Islam by always strengthening the faith and piety, so as to be useful human beings for the state, religion and achieve happiness of the world and the hereafter. Vocabulary education is philosophically oriented towards Islamic values based on three dimensions, (a) inculcating a balanced and harmonious relationship with God, (b) establishing a harmonious, harmonious and balanced relationship with the community, (c) developing the ability to explore, managing, and utilizing the natural wealth for the benefit of the welfare of his life with a harmonious attitude.